P122 Myeloid-derived suppressor cells as a potential biomarker and therapeutic target in rhino-orbital mucormycosis patients. (20th September 2022) - Singh, Praveen; Das, Shukla; Rai, Gargi; Ansari, Mohammad Ahmad; Gupta, Neelima; Sharma, Sonal
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Background: Mucormycosis is a deadly fungal infection that emerges in patients affected with COVID-19. All fungal illnesses are caused by dysregulated adaptive immunity, but Myeloid-derived suppressor cells (MDSC) have added a new dimension to the chronic inflammatory response. Objective: We attempted to enumerate the MDSC immune response in rhino-orbital mucormycosis patients before and after treatment and compared the data with healthy control. Methods: A total of 3 ml of blood samples were taken in an EDTA vial from 20 patients with mucormycosis and 20 age-matched healthy control. A second blood sample was collected to examine the immune system post three months of treatment. Mycological identification was performed on nasal crust retrieved after surgery using KOH/culture. The expression of the MDSC marker was analyzed by immunostaining with the antibodies against CD14, HLA-DR, CD11b, CD33, CD66 (Biolegend). Fluorescence profiles were recorded by Flow Cytometer (BD FACSAria™ III) and analyzed by Flow Jo software (BD Biosciences). The percentage of positive cells is used to express the results. The GraphPad Prism (version 8, GraphPad software, LaJolla, CA, USA) was used to analyze the data. All of the results were considered significant when P <.05. Results: All of the patients tested positive for Rhizopus arrhizus, which was confirmed by the culture. The percentages of Monocytic-MDSC (mMDSC: CD14 + HLA-DR-/low) cells were significantly high in patients compared to healthy control. In post-3-month treatment, the percentages of mMDSC were found significantly low and comparable with healthy control. Granulocytic MDSC (gMDSC: HLA-DR-/low CD33 + CD11b + CD66+) cell population was higher in patients compared with healthy control and patients with post-3-month treatment. Conclusion: MDSC regulates T cells and other immune cells with a different mode of action. The findings in this study imminently indicate the mechanism of immune dysregulation involving MDSC pathways in mucormycosis and provide evidence that restoration of immune balance causes reduction of MDSC cells may be considered a therapeutic option for long-term benefit.